Countering cyber attacks and preserving the integrity and availability of critical systems - Geetha, S. 1979; Phamila, Asnath Victy 1978 (Advances in digital crime, forensics, and cyber terrorism (ADCFCT) book series, 2019)
"This book focuses on advances in theory, design and development, implementation, analysis, empirical evaluation and verification of cyber security systems. It also explores advances in cyber security that will help in thwarting future sophisticated attacks, vulnerability-threats, data-breaches, fraud, and system-damage"--